BASIC ENGINEERING CONSIDERATIONS FOR ENGINEERS AND ENTREPRENEURS - Arun Chnadra Sawhney (PREPARE@u® | IEI Conferences, 2021)
It has been found that our engineering education system lacks imparting an holistic approach and entrepreneurship skills which does not prepare them fit for setting up a new venture  or solve day to day engineering problems in an holistic manner.Our formal engineering education system shall inculcate a holistic engineering thinking in the minds of young engineers so that they are trained in such a manner to tackle any kind of engineering challenges in future with ease. This holistic approach means that once any engineer applies the basic engineering considerations given in this paper to any project/venture/ system then he is sure that he has not left any major technical glitch.This paper deals with all the basic engineering considerations required for engineers to think like an engineer in a holistic manner which will prepare them to become a successful entrepreneur.